Muscle activation intensity during running in barefoot adapted subjects - Azevedo, A. P.; Valvassori, R.; Mezêncio, B.; Claudino, J. G. O.; Pennone, J.; Anjos, F. O. M.; Souza, M. A.; Amadio, A. C.; Serrão, J. C. (International Calgary Running Symposium, August 14-17, 2014, 2014)
There is evidence that the human body is capable of adapting to barefoot locomotion 2-4. One hypothesis is to find similar or smaller muscle activation intensity in barefoot compared to shod running. The present study analyzed the muscle activation intensity in 6 runners (3 male and 3 female, 29.5 ± 7.3 years, 64.1 ± 11.0kg, 1.68 ± 0.14m) who had, at least, 4-months experience in barefoot locomotion. They ran during 10 minutes, at 9 km/h on a treadmill, in shod and barefoot conditions. Nine data acquisitions (10 seconds each - 2600Hz) of EMG signals were performed (EMG 100 - Lynx System) from the tibialis anterior, gastrocnemius lateralis, rectus femoris, vastus lateralis, and biceps femoris for each condition. The RMS was calculated for the stance phase. Data was normalized by the maximum voluntary isometric contraction (MVIC). A one-way ANOVA for repeated measures was performed (p <0.05). No significant differences were found between shod and barefoot conditions for the muscles analyzed. Although non adapted subjects have been found to have greater muscle activation intensity in barefoot compared to shod running1, our results suggest that once runners are adapted to barefoot running, muscle activation patterns are similar for both experimental conditions. We conclude that muscle activation intensity of the lower limbs is similar between shod and barefoot running in subjects who are adapted to barefoot locomotion.